2017
DOI: 10.1371/journal.pgen.1006935
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific insulin signaling mediates female sexual attractiveness

Abstract: Individuals choose their mates so as to maximize reproductive success, and one important component of this choice is assessment of traits reflecting mate quality. Little is known about why specific traits are used for mate quality assessment nor about how they reflect it. We have previously shown that global manipulation of insulin signaling, a nutrient-sensing pathway governing investment in survival versus reproduction, affects female sexual attractiveness in the fruit fly, Drosophila melanogaster. Here we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Insulin signaling also regulates absorption of nutrients by the fat body. This tissue produces yolk proteins that will be taken up by the developing oocyte; yolk protein production is thus a major limiting step in oocyte maturation and hence fecundity (Fedina et al 2017). Interestingly, under conditions of low insulin, where resources in the fat body may be released to fuel egg production, the females’ oenocytes reduce production of the CHs 7-T and ( Z )-5-Tricosene (5-T)(Fedina et al 2017).…”
Section: Female-derived Pheromones That Mediate Virgins’ Attractivmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin signaling also regulates absorption of nutrients by the fat body. This tissue produces yolk proteins that will be taken up by the developing oocyte; yolk protein production is thus a major limiting step in oocyte maturation and hence fecundity (Fedina et al 2017). Interestingly, under conditions of low insulin, where resources in the fat body may be released to fuel egg production, the females’ oenocytes reduce production of the CHs 7-T and ( Z )-5-Tricosene (5-T)(Fedina et al 2017).…”
Section: Female-derived Pheromones That Mediate Virgins’ Attractivmentioning
confidence: 99%
“…This tissue produces yolk proteins that will be taken up by the developing oocyte; yolk protein production is thus a major limiting step in oocyte maturation and hence fecundity (Fedina et al 2017). Interestingly, under conditions of low insulin, where resources in the fat body may be released to fuel egg production, the females’ oenocytes reduce production of the CHs 7-T and ( Z )-5-Tricosene (5-T)(Fedina et al 2017). This is intriguing because these two CHs, which are normally produced at higher levels in males than in females, had previously been associated with reducing male-male courtship, suggesting that they may play a role in decreasing the attractiveness of any fly to a romantically-inclined male (Billeter et al 2009; Ferveur and Sureau 1996; Lacaille et al 2007; Wang et al 2011).…”
Section: Female-derived Pheromones That Mediate Virgins’ Attractivmentioning
confidence: 99%
“…Although the dual-luciferase reporter gene assay suggested that BgDsx M can directly regulate the transcript of BgElo12 , there may be other indirect regulatory pathways. Several candidate factors have been shown to regulate the HC profiles in various insects (e.g., D. melanogaster ), including ecdysone, juvenile hormone (JH), biogenic amines, and the insulin signaling pathway (Wicker et al, 1995a; 1995b; Marican et al, 2004; Kuo et al, 2012; Bontonou et al, 2015; Fedina et al, 2017; Baron et al, 2018). These connections are highlighted by ecdysone, which is mainly produced by the prothoracic gland, but in some insects also by the ovaries (Bownes and Smith, 1984; Romaá et al, 1995), and the development of the ovaries is under the regulation of the sex-differentiation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the responses to plant odors are often enhanced after mating, as females must find a suitable oviposition site (Gadenne et al 2016). Even though the endocrine modulation of female behavior has been less studied than that in males, there is a crucial role of hormones in regulating the production of pheromones, sexual attractiveness and the temporal organization of sexual behavior in female moths (Fedina et al, 2017;Bloch et al 2013). DEHP could interact with this hormonal regulation in S. littoralis to induce the disruption of female behaviors.…”
Section: Discussionmentioning
confidence: 99%